Negotiating Femininities in the Neoliberal Night-Time Economy Too Much of a Girl? - Nicholls, Emily; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book explores the ways in which young women negotiate gendered and classed identities in nightlife venues. With a particular focus on the under-researched phenomenon of the 'girls' night out', this text explores tensions around what it means to be 'girly' in bars, pubs and clubs, examining throughout the ways in which being a 'girly girl' is simultaneously desired and derided in a postfeminist context. Drawing on research conducted in Newcastle-upon-Tyne, UK, this original and comprehensive book explores the value and meaning of the 'girls' night out' for young women, and its instrumental role in the negotiation of friendships and femininities. Nicholls covers a range of themes, including alcohol consumption, dress, and risk management, providing engaging and timely insights into women's leisure as a site for the negotiation of gendered identities. Negotiating Femininities in the Neoliberal Night-Time Economy will be of interest to students and scholars acrossthe social sciences with an interest in gender, class and the Night-Time Economy.
Introduction -- Carefree or Controlled? Understanding the Night-Time Economy -- 'It's Girl Time': Girliness and Friendships -- 'Rowdy...? That's the Whole Point of Going on a Night Out': Time Out, Transgression and Control -- 'What Else About Her Is Fake?': 'Emphasised' Femininity,Authenticity and Appearance -- 'People Don't See You if You're a Woman and You're Not Really Dressed Up': Visibility and Risk -- Conclusion.
Keywords: Ethnology; Feminism; Feminist theory; Sports -- Sociological aspects; Sociocultural Anthropology; Feminism and Feminist Theory; Sport Sociology